THE POWER RUBBER PRODUCTS WITH THE PREDICTABLE DEFORMATION CHARACTERISTICS FOR PICKING TROLLEYS OF DOMESTIC PASSENGER CAR - Skokov, O. I.; Bespalova, L. V.; Diachenko, O. H.; Politaieva, D. L.; Skorykova, T. S. (Science and Transport Progress, 2008)
The works on creation of the design, production technology and testing procedures for large-sized power rubber technical products making up a set of the bogie for a passenger coach are performed.